Inhibiting Factors in Beginning Reading Ability of Class I Elementary School Students - Afifah Nur Fadhilah; Ade Hikmat (Jurnal Paedagogy, 2022)
This study aims waas to describe the inhibiting factors for early reading in grade 1 elementary school students and find the right solution to overcome these students' early reading difficulties. The type of research used was escriptive qualitative with case study method. The subjects in this study were IC class students at SDN Srengseng Sawah 15 Pagi totaling 32 students. Data collection techniques in this study were observation, interviews with (teachers, students and parents of students) and documentation. Data analysis technique was one by data reduction, data presentation and conclusion drawing. The results of this study indicate that the inhibiting factors for early reading in grade I students at SDN 15 Pagi South Jakarta include: 1). Factors of interest in reading students who are still very lacking, (2). Family factors become significant influencing students' reading ability 3). Environmental factors where they come from effect the development of children. Solutions that can overcome the difficulties of early reading are: (1) Teachers provide additional study hours for children to learn to read, (2) Parents must give attention, motivation and encouragement to children, (3) The home environment, the need to limit and monitor children in playing and provide learning facilities at home for children.